Pedagogical Challenges and Impacts of the Merdeka Curriculum for Students with Special Needs - Novembli, Meta Silfia; Wahyuni, Sri; Hasanah, Nisaul; Fitriani, Dina; Hartati, Peby Tri (International Journal of Pedagogy, 2025)
This study explores the challenges and impacts of the Merdeka Curriculum implementation in Special Needs Schools (SLB) in Pekanbaru on students with special needs. Using a quantitative survey method with a total sampling approach involving SLB teachers in Pekanbaru (n45), data was collected through questionnaires, interviews, and documentation. The analysis utilized Descriptive Statistics and Qualitative data analysis was conducted on interview transcripts and documents. The research results indicate significant challenges in teacher readiness (65% need more training, 25% low), availability of resources and infrastructure (70% minimal), and curriculum and assessment adaptation (60% difficulty in adaptation, 55% difficulty in assessment), with most falling into the "Moderate" to "High" categories. Nevertheless, the Merdeka Curriculum shows a positive impact on social development (65% increase in communication and participation) and student engagement (70% increase in motivation and active participation) which are in the "Moderate" to "High" categories. However, students' academic development is still limited to the "Moderate" category. This study highlights the need for more specific teacher training, provision of adequate resources, and targeted curriculum adaptation strategies to optimize the potential of the Merdeka Curriculum in supporting inclusive education in SLB.